On PPP, unit roots and panels - Martin Wagner (Institute for Advanced Studies (IHS), 2005)
This paper re-assesses the panel (unit root test) evidence for PPP on four monthly data sets. We discuss and illustrate that commonly-used first generation panel unit root tests are inappropriate for PPP analysis since they are constructed for cross-sectionally uncorrelated panels. Given that real exchange rate panel data sets are - almost by construction - highly cross-sectionally correlated, so called second generation panel unit root methods that allow for and model cross-sectional dependence should be applied. Using inappropriate first generation tests, quite strong evidence for PPP is found. However, this evidence vanishes entirely when resorting to an appropriate method (e.g. the one developed in Bai and Ng, 2004a) for nonstationary cross-sectionally correlated panels. We strongly believe that our findings are relevant beyond the data sets investigated here for illustration.
Keywords: C23; F30; F31; 330; PPP; real exchange rate index; unit root; panel; cross-sectional dependence; factor model; Kaufkraftparität; Unit Root Test; Faktorenanalyse; Panel